Sharia Dynamics Islamic Law and Sociopolitical Processes - Daniels, Timothy P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This multidisciplinary volume explores the role of Islamic law within the dynamic processes of postcolonial transformation, nation building, and social reform. Here, eleven international scholars examine Islamic law in several contemporary sociopolitical contexts, focusing specifically on Malaysia, Indonesia, Pakistan, China, Tunisia, Nigeria, the United States, and the International Islamic Fiqh Academy (IIFA) of the Organization of Islamic Cooperation (OIC). The contributors also address the entanglement of Islamic law and ethics with the history of Muslim religious discourses, shifts toward modernity, gender relations, and efforts to construct exclusive or plural national communities. Sharia Dynamics, at once enchanting and enlightening, is a must-read for scholars of contemporary Islam. .
1. Introduction: Sharia Dynamics and the Anthropology of Islam -- 2. Fatwa, Discursivity, and the Production of Sharia -- 3. Fatwās on Mohamed Bouazizi's Self Immolation: Religious Authority, Media, and Secularization -- 4. Sharia Law and Muslim Ethical Imaginaries in Modern Indonesia -- 5. Sharia in China: Compromising Perceptions -- 6. Interplay of Sharia Projects: Between Ketuanan Melayu, Islam, and Liberal Rights in Malaysia -- 7. Gendered Accounts of Expertise within Islamic Finance and Financialization in Malaysia -- 8. The Difficulty of Accounting for Women Who Critique Sharia in Northern Nigeria -- 9. Islamic Movements, Women, and Social Reform: Who Speaks of the Sharia in Pakistan? -- 10. You Are Not a Muslim: Ahmadiyya Exclusion and Sharia Interpretation in Pakistan -- 11. Anwar and Maqasid: Forging a Muslim Democracy -- 12. A Veneer of Unity? Islam and a Culture of Inclusion in Sabah.
Keywords: Ethnology; Religion and sociology; Islam